2017
DOI: 10.1128/aac.00082-17
|View full text |Cite
|
Sign up to set email alerts
|

Demonstrating the Protective Efficacy of the Novel Fluoroquinolone Finafloxacin against an Inhalational Exposure to Burkholderia pseudomallei

Abstract: Burkholderia pseudomallei is the causative agent of melioidosis, a serious disease endemic in Southeast Asia and Northern Australia. Antibiotic treatment is lengthy and relapse often occurs. Finafloxacin is a novel fluoroquinolone with increased antibacterial activity in acidic conditions in contrast to other fluoroquinolones which demonstrate reduced activity at a lower pH. Therefore, finafloxacin may have improved efficacy against B. pseudomallei, which can survive within host cells where the local pH is aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 43 publications
3
28
0
Order By: Relevance
“…Ciprofloxacin was shown to be bacteriostatic at both pHs. Although finafloxacin did not show superior activity in a time kill assay at pH 6 when compared to pH 7, it was able to rapidly kill bacteria (almost 3 logs in 4 h), a finding previously reported for B. pseudomallei (Barnes et al, 2017). This result correlates well with other published work with finafloxacin and other bacterial species in vitro (Higgins et al, 2010; Lemaire et al, 2011).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Ciprofloxacin was shown to be bacteriostatic at both pHs. Although finafloxacin did not show superior activity in a time kill assay at pH 6 when compared to pH 7, it was able to rapidly kill bacteria (almost 3 logs in 4 h), a finding previously reported for B. pseudomallei (Barnes et al, 2017). This result correlates well with other published work with finafloxacin and other bacterial species in vitro (Higgins et al, 2010; Lemaire et al, 2011).…”
Section: Discussionsupporting
confidence: 64%
“…An intravenous preparation of ciprofloxacin (Ciproxin 2 mg/ml) was purchased from Bayer (Basingstoke, United Kingdom). Dosing regimens were determined using pharmacokinetic data generated from previous studies (Barnes et al, 2017; Hamblin et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison to ciprofloxacin, significantly increased potency of BFX was observed during intracellular but not extracellular growth, suggesting an ability to achieve higher concentrations of active compound in mammalian cells. If true, further study is warranted to determine if this is due to enhanced membrane permeability, a lower isoelectric point and increased activity in acidic compartments such as the phagolysosome (60, 61), or some other mechanism. A comprehensive assessment of BFX’s spectrum of activity, particularly against other intracellular pathogens such as Shigella and Salmonella , may be informative and clinically relevant in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…The availability of formulations of finafloxacin that can be delivered orally and systemically makes finafloxacin a worthy alternative for the treatment of a range of infections. In addition to good safety and efficacy data obtained in patients suffering from complicated urinary tract infections and pyelonephritis, previous studies have also demonstrated efficacy against the biothreat agents Burkholderia pseudomallei and Francisella tularensis in vitro and in vivo (6, 911). The aim of this study was to further evaluate the in vitro activity of finafloxacin against larger strain panels of biodefense pathogens.…”
Section: Textmentioning
confidence: 96%